Serum Superoxide Dismutase And Paraoxonase-1 Activity In Preeclampsia Patients - ANIL B. BARGALE; JAYASHREE V. GANU; DHIRAJ J. TRIVEDI; PRAMOD S. KAMBLE; RAKESH MUDARADDI (International Journal of Pharma and Bio Sciences, 2011)
Preeclampsia (PE) is a multisystem disorder characterized by hypertension, proteinuria and edema. Endothelial cell (EC) injury plays an important role in the pathogenesis of PE. The antioxidant enzyme SOD is a scavenger of superoxide anion and prevents oxidative damage of EC. Dysfunction of EC is associated with dyslipidemia due to oxidation of LDL, which is lowered by the enzyme PON-1. The aim of present study is to determine superoxide dismutase and paraoxonase-1 activity in preeclamptic women. In this study we found that serum SOD and PON-1 activity was decreased in preeclamptic women (3.614±0.539, 45.815±4.725) as compared to normal pregnant women (5.796±1.242, 65.012±6.318). But, SOD and PON-1 activity in between mild and severe PE women’s were not-significant. Our observed results show decrease in the antioxidant SOD and PON-1 activity point towards their role in the pathogenesis of PE.